Cushioning the blow: role of perirenal fat in renal trauma injury severity. (2nd August 2022) - Hakam, Nizar; Lui, Jason L.; Shaw, Nathan M.; Breyer, Benjamin N.
Abstract : Objectives: To explore the association between perirenal fat thickness (PFT) and renal trauma grade. We hypothesise this association is related to a shock‐absorbing effect of adiposity around the kidney. Patients and Methods: We identified all patients with renal trauma who arrived at the emergency department of a single trauma centre between 2014 and 2020. Radiology images were reviewed to measure the PFT around the uninjured kidney due to disrupted PFT around the traumatised kidney. Patients with no available images or penetrating trauma mechanism were excluded. Logistic regression was used to assess the relation between PFT and high‐grade renal trauma (HGRT; defined as American Association for the Surgery of Trauma Renal Grade IV–V), adjusting for age, sex, and Injury Severity Scale (ISS). Results: A total of 150 patients with renal trauma were included. The median (interquartile range) age was 38.5 (26–52) years and 106 (70.7%) were males. The PFT ranged between 2.1 and 50.1 mm, and 31 (20.7%) had HGRT. Interestingly, PFT only mildly correlated with body mass index (BMI; Pearson correlation coefficient 0.42, P < 0.001). Those with HGRT had significantly lower PFT compared to those without HGRT (median 9.5 vs 11.9 mm, P = 0.047). In the multivariable analysis adjusting for age, sex, and ISS, increasing PFT was associated with decreased odds (odds ratio 0.91, 95% confidence interval 0.84–0.98; P = 0.015) of HGRT. Conclusion: Increasing PFT is associated with lower risk of HGRT following blunt injury. These results support a protective cushion role of adiposity in renal trauma. Notably, PFT was not strongly correlated with BMI, underscoring limitations of BMI in measuring adiposity.